Screening and evaluation of variables for determination of sulfonylurea herbicides in water samples by capillary zone electrophoresis - Springer, Valeria Haydee (2016)
A simple and rapid capillary electrophoretic method was developed for the simultaneous determination of two sulfonylurea herbicides in water samples: metsulfuron-methyl (MSM) and nicosulfuron (NS). These herbicides are widely used in agricultural practices and their residues represent potential environment pollutants in waters and soils. The effect of the pH of the background electrolyte solution (BGE), the percentage of methanol in the BGE and the separation voltage were studied on the resolution of MSM and NS. A 23 factorial design was used to identify the main factors which significantly influenced the separation of these compounds. Other parameters were evaluated by the univariate method. The experimental results show that using a BGE composed of 25 mmol·L−1 sodium borate and 3% (v/v) of methanol at pH 8.5 and applying 15 kV, satisfactory analysis time and resolution between peaks can be obtained. The linear range for both analytes was 0.1–2.0 µg·mL−1. The detection limits were 0.034 µg·mL−1 for MSM and 0.044 µg·mL−1 for NS. Surface water and groundwater samples were analyzed applying the new method, and the obtained results presented satisfactory recovery percentages (82%–102%).